Knowledge and learning in virtual communities of practice (VCoPs): Theoretical underpinnings - Liashenko, Maria (Proceedings of the International Conference on Networked Learning, 2018)
The aim of the paper is to revisit the concepts of knowledge and learning in virtual communities of practice (VCoPs). Despite a great variety of approaches and successful examples of deployment of VCoPs, little research attention is paid to developing models or frameworks conceptualizing knowledge and learning in VCoPs. The review of the selected literature has enabled to propose a multi metaphorical framework of knowledge and a conceptual model of learning in VCoPs. The author uses a metaphoric approach to address the idea of paradigm shift and suggests a non-linear perspective on knowledge evolution affected by technological innovations. The multi metaphorical framework under consideration shows the shifts from behavioral learning to networked learning where VCoPs are located. The definition of VCoPs and their features are paid special attention to in the research. VCoPs are viewed from three overlapping dimensions: Community of practice, virtual domain of technology enhanced learning and discipline-based learning community of practice. Such a view represents a conceptual idea of discipline-based VCoPs which arises when three main components interplay: domain (virtual environment where teacher-student social interaction takes place); the community (the principles of apprenticeship as a learning model); the practice (developing the repertoire to solve problems within the discipline context). Also, the suggested multi metaphorical framework enables viewing learning within VCoP from knowledge- creation metaphor which leads to examination of learning from the perspectives of activity theory. Activity theory is used not as an analytical tool in the research but mainly as a descriptive approach to delineate learning within VCops as a technology mediated activity. The knowledge is constructed within the community, but the interaction and learning are mediated via digital artifacts. Applying principles of activity theory, VCoPs can be analyzed as complex systems where subjects interact with the community using technologies. Systems approach is applied to work out a logical model of learning activity in VCoPs consisting of axiological, cognitive, professional-educational, technological, communicative, reflexive components. The proposed model should be considered as a schematically descriptive model of learning within VCoPs because complex systems cannot be perceived using one approach due to their multidimensional and complex nature. The paper concludes by the discussion of the findings and recommendations for further research. The topic is of interest because better understanding of the concepts of knowledge and subsystems of learning concept in the era of technologies is sure to enhance teaching practice.